UMPSA participates in the 67th National Day parade in Kuantan and Pekan - Naqiah, Puaad (UMPSA, 2024)
KUANTAN, 31 August 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) sent two contingents to participate in the parade for the 67th National Day Celebration at the Pahang State Level in Kuantan and Pekan.